Kohesivitas Kelompok Sebagai Pemoderasi Pengaruh Partisipasi Penganggaran, Asimetri Informasi, dan Self Esteem Pada Senjangan Anggaran - Yuna Aditya, Nyoman Putra; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2019)
Budgeting activities are carried out as a measure of manager's performance, there tends to be a discrepancy between the budgeted and realized as stated by several BPR leaders in the city of Denpasar. The purpose of this study was to obtain empirical evidence of the influence of group cohesiveness in moderating the effect of budget participation, information asymmetry, and self esteem on budgetary slack. The population in this study were all officials or employees involved in the budgeting process for 21 BPR in Denpasar City. Samples were taken using purposive sampling technique. The analysis technique used is Moderated Regression Analysis (MRA). Based on the results of the study, group cohesiveness was not able to moderate the effect of budgetary participation on budgetary slack, but group cohesiveness was statistically able to moderate the influence of information asymmetry and self esteem on budgetary slack in rural banks throughout the city of Denpasar. Keywords : Budget participation, information asymmetry, self esteem, budgetary slack.